Evaluation of osteogenic potential of demineralized bone matrix in pigeon (Columba livia Gmelin) - Sanaei, Mohamad Reza (2011)
Bone fractures are among the most frequent tragedies crippling a large number of birds every year. Unfortunately, many of these birds will not be able to get back to the wild or have to be euthanized due to a wide range of complications. Despite the dearth of cancellous bone in avian species, there are currently no reliable alternatives to autologous bone grafting techniques available. Thus this study was undertaken to evaluate implants of demineralized bone matrix (DBM) in a pigeon model. In order to do so, DBM was evaluated in both heterotopic and orthotopic sites.In heterotopic study, two forms of allogenic DBM comprised of tubular DBM (TDBM) and chipped DBM (CDBM) were implanted bilaterally into the superficial pectoral muscles in 24 pigeons (Columba livia). Autologous bone marrow which is known to produce ectopic bone in mammals was implanted in a third site. A fourth intramuscular site served as a negative control and was irrigated with normal saline before closure. Birds were euthanized in batches at 1, 4, 6, 8, 10, and 12 weeks following implantations to histologically evaluate the fate of implants. Unlike previous studies in mammalian models, bone marrow failed to produce de novo bone formation in this pigeon model. Instead, statistical analysis of semi-quantitative and quantitative histologic data revealed a significant difference from controls in the extent of neovascularization in favor of the bone marrow after 6 and 10 weeks. All DBM explants showed new bone at retrieval with the exception of tubular implants at first week. The most reactive part of the implants was found to be their interior area between the periosteal and endosteal shells followed by the area at the implant-muscle interface. Nevertheless the latter was mostly associated with the DBM chips. On the other hand, quantitative measurements showed the overall amount of new bone to be greater at the TDBM implant sites (80.28% ± 8.94) and chipped DBM showed to be significantly inferior in this regard (57.64% ± 3.12).In the second experiment, osseous critical sized defects were surgically created in the ulnar midshafts of 60 adult pigeons in which TDBM or CDBM implants served to augment the healing process. Autologous bone graft (ABG), harvested from the sternal keel was used in a third control group. Created fractures were stabilized using an external skeletal fixator-intramedullary tie-in device. Results were evaluated by radiography and histology after 4, 8, 12 and 24 weeks postoperatively. Although ABG group demonstrated greater improvement in comparison to DBM groups early in the course of this study, they failed to advance after the eighth postoperative week with the overall radiographic score of 2.95 ± 0.15, histological score of 6.87 ± 0.44 and bone area of 68.41 ± 3.79. Conversely, both DBM groups and particularly TDBM demonstrated promise with regards to their continuous improvement over time. Nevertheless, CDBM proved to be inferior to TDBM in overall healing qualities with overall radiographic score of 1.5 ± 0.11, histological score of 5.37 ± 0.32 and bone area of 41.32 ± 3.83. Despite the early dominance of ABG, TDBM finally overtook autografts after week 12 and such was proved to be significant by 24 postoperative week (2 fractures fully healed versus only one complete healing for ABG). However the overall average of values for this group remained lower than that of the ABG (radiographic score of 2.40 ± 0.21, histological score of 8.07 ± 0.77 and bone area of 59.3 ± 7.47).This study showed that avian DBM is an osteoinductive, biocompatible, biodegradable, safe and osteoconductive material in pigeons. Results from the orthotopic study showed promise as TDBM implants appeared as efficacious as autografts in the healing of osseous critical sized defects. This confirmed that implant geometry (shape and size) could affect DBM associated osteogenesis in avian species. We suggested osteoconduction augments the magnitude of the effects in larger implants.